DEAD box RNA helicases act as nucleotide exchange factors for casein kinase 2 - Fatti, Edoardo; Hirth, Alexander; Švorinić, Andrea; Günther, Matthias; Stier, Gunter; Cruciat, Cristina-Maria; Acebron, Sergio P.; Papageorgiou, Dimitris; Sinning, Irmgard; Krijgsveld, Jeroen; Höfer, Thomas; Niehrs, Christof (Science signaling, 2023)
DDX RNA helicases promote RNA processing, but DDX3X also activates casein kinase 1 (CK1ε). We show that other DDX proteins also stimulate the protein kinase activity of CK1ε and that this extends to casein kinase 2 (CK2). CK2 enzymatic activity was stimulated by various DDX proteins at high substrate concentrations. DDX1, DDX24, DDX41, and DDX54 were required for full kinase activity in vitro and in Xenopus embryos. Mutational analysis of DDX3X indicated that CK1 and CK2 kinase stimulation engages its RNA binding but not catalytic motifs. Mathematical modeling of enzyme kinetics and stopped-flow spectroscopy showed that DDX proteins function as nucleotide exchange factors toward CK2 and reduce unproductive reaction intermediates and substrate inhibition. Our study reveals protein kinase stimulation by nucleotide exchange as important for kinase regulation and as a generic function of DDX proteins.